A Overview of The Implementation of Discharge Planning by Nurses in The 3th Class Inpatient Room of Jember Hospital - Vinolia, Veni; Yuwanto, Mahmud Ady (Blambangan Journal of Nursing and Health Sciences (BJNHS), 2024)
Background: Discharge planning is a dynamic and systematic process of assessment, preparation, and coordination carried out to convey the ease of supervision of health services and social services before and after discharge. Objective: To find out the picture of the implementation of discharge planning by nurses in the class 3 inpatient room. Method: Data collection techniques used in this final scientific work using observation, interviews, documentation and checklists. Results: In this scientific work, the implementation of discharge planning by nurses in the 3th class inpatient rooms is not optimal. Conclusions and suggestions: The implementation and documentation of discharge planing by nurses in class 3 inpatient rooms has not been optimal which is caused by several factors, one of which is the majority of nurse education that is still Diploma Nursing and there are several obstacles in documenting discharge planning, namely: human resources who carry out discharge planning do not understand the importance of discharge planning, the unavailability of appropriate SOPs and discharge planning guidelines and the unavailability of appropriate discharge planning forms